Synergistic developmental toxicity and apoptosis of BPA and Zn Co-exposure in Daphnia magna - Naima Hamid,; Aishah Arifin,; Ong, Meng Chuan (Penerbit Universiti Kebangsaan Malaysia, 2024)
The combined effects of chemical pollutants in the aqueous environment create inevitable impacts on aquatic ecosystems. Bisphenol A (BPA) is identified as a chemical pollutant of significant concern, primarily owing to its pronounced toxicity in the freshwater environment. Similarly, essential elements like zinc (Zn) may induce toxic effects upon alterations in their metal speciation, leading to increased bioavailability. Therefore, the present study aimed to elucidate the developmental toxicity effects using fresh water model Daphnia magna. Using environmentrelevant BPA (10 µg/L and 20 µg/L) and Zn (10 µg/L and 30 µg/L) levels were exposed to Daphnia magna for 48 h to determine the acute toxicity. Results showed that maximum mortality (40%) was observed at a high exposure dose of BPA and Zn at 48 h. Similarly, a significant dose-dependent reduction in heartbeat and body weight was found in all samples. Blood clotting, broken antenna, missing tail changes in the carapace, and bioaccumulation, were the dominant morphological changes in all treatments. These findings were confirmed with the elevated apoptosis at the second antenna, gut, and post-abdominal regions after high-dose treatment. Spearman correlation analysis showed a significant positive correlation (R2 = 0.86) between mortality and deformity ratio indicating high joint toxicity of BPA and Zn. Lastly, more in-depth studies are required to highlight the combined toxicity of the BPA and Zn and ensure ecological integrity.